Tantangan dan Solusi Terkini dalam Penanganan Penyakit Menular - Putri, Titania (Surabaya Biomedical Journal, 2024)
Infectious disease management continues to face various dynamic challenges along with environmental changes, human travel patterns, and the emergence of new pathogens. This study aims to analyze and identify current challenges and the solution in infectious disease management through a literature review method. The review covered scientific literature from various relevant sources, including journals, books, and reports from international health organizations. The results of this study show that the main challenges include antimicrobial resistance, and lack of health infrastructure in some regions. In addition, global issues such as climate change and urbanization exacerbate the situation by increasing the risk of disease spread. The study also found that international collaboration, innovations in medical technology, and increased public awareness and education are key to overcoming these challenges. In conclusion, addressing infectious diseases requires a multidisciplinary and cross-sectoral approach to improve the global response to evolving health threats.